2020
DOI: 10.3390/polym12071539
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hydrophobic Surface on PLA and ABS by Fused Deposition Modeling

Abstract: In the fields of agriculture, medical treatment, food, and packaging, polymers are required to have the characteristics of self-cleaning, anti-icing, and anti-corrosion. The traditional preparation method of hydrophobic coatings is costly and the process is complex, which has special requirements on the surface of the part. In this study, fused deposition modeling (FDM) 3D printing technology with design and processing flexibility was applied to the preparation of hydrophobic coatings on polylactic acid (PLA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 32 publications
2
14
0
1
Order By: Relevance
“…The highest surface roughness was determined on non-sanded substrates, particularly PLA-W, followed by PLA and ABS. As reported by Yang and co-authors [53], the layer thickness and filling method have a significant effect on the surface roughness of the 3D-printed parts, while the printing speed has no effect on the surface roughness.…”
Section: Surface Roughnessmentioning
confidence: 54%
“…The highest surface roughness was determined on non-sanded substrates, particularly PLA-W, followed by PLA and ABS. As reported by Yang and co-authors [53], the layer thickness and filling method have a significant effect on the surface roughness of the 3D-printed parts, while the printing speed has no effect on the surface roughness.…”
Section: Surface Roughnessmentioning
confidence: 54%
“…The explanation of the increase of hydrophobicity in B-OH is not intuitive. The inhomogeneity of surface mechanical properties ( Figure 11 , Figures S10 and S11 ) might correspond to a slightly higher surface roughness and thus an increase of hydrophobicity (e.g., [ 63 ]), but full clarification requires more detailed studies. The observed increase of the polar component may be related to the presence of silsesquioxane structures on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The strength and microstructure were reported to be improved, and a desirable bonding interface was also achieved with the carbon fiber addition. Yang et al (2020) have reported that the layer height and method of filling contributed a major effect on the surface roughness of PLA and ABS material properties. Sanatgar et al (2017) had prepared the PLA nanocomposite specimens, and from the investigation, it was concluded that the temperature of the extruder, platform, and print speed had a significant impact on the adhesion force of printed fabrics or nanocomposites.…”
Section: Introductionmentioning
confidence: 99%